Does high adherence to contact precautions lead to low in-hospital transmission of multi-drug-resistant micro-organisms in the endemic setting?. (October 2021) - Büchler, A.C.; Dangel, M.; Frei, R.; Jäger, S.; Roth, J.A.; Seth-Smith, H.M.B.; Egli, A.; Widmer, A.F.
Summary: Background: Conflicting results have been published on the impact of contact precautions (CPs) on reduction of transmission of multi-drug-resistant micro-organisms (MDROs) in the endemic setting. Ambiguous definitions coupled with low adherence partly explain these differences. Aim: We prospectively monitored the level of adherence to CPs and aimed to relate it to in-hospital transmission of MDROs. Methods: Between January 2016 and March 2018, all patients under CPs underwent continuous monitoring of adherence to CPs by routine on-site visits on days 0, 3 and 7 after initiating CPs using a standardized checklist. The protocol included 10 interventions that were routinely checked such as CP sign at the door as well as wearing of gowns and gloves upon entry to the patient room. Patients requiring CPs were defined as colonized or infected with MDROs (meticillin-resistant Staphylococcus aureus (MRSA), non- Escherichia coli extended-spectrum beta lactamase (ESBL) Enterobacterales, vancomycin-resistant enterococci (VRE) and carbapenem-resistant Gram-negative micro-organisms (CRGN)) as well as patients infected with respiratory viruses, norovirus, scabies and hypervirulent strains of Clostridioides difficile . Findings: Overall, data from 13, 756 CP records from 1378 visits of 812 patients were analysed. Adherence varied between 93% and 100% for each intervention, except for "separate space for contaminated material" with an adherence of 5.3–6.1%. The incidence of in-hospital transmission during the study period was extremely low for MRSA, VRE, non- E.coli ESBL Enterobacterales and CRGN with 0.00–0.064 cases/1000 patient days. Conclusion: High adherence coupled with continuous monitoring of CPs correlated with a very low in-hospital transmission rate. These results indicate that CPs are highly effective if routine monitoring of adherence is implemented.